Specifics of family relations and emotional relationships in families of the women with paranoid schizophrenia - Driuchenko, M. (Journal of Education, Health and Sport, 2016)
Driuchenko M. Specifics of family relations and emotional relationships in families of the women with paranoid schizophrenia. Journal of Education, Health and Sport. 2016;6(10):810-820. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.265724 http://ojs.ukw.edu.pl/index.php/johs/article/view/4216 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. UDK 616.895.87-055.52:616-056.2./76 SPECIFICS OF FAMILY RELATIONS AND EMOTIONAL RELATIONSHIPS IN FAMILIES OF THE WOMEN WITH PARANOID SCHIZOPHRENIA M. Driuchenko Uzhgorod National University, Ukraine Summary The objective: to analyze the specifics of family relationships and emotional relationships in families of women with paranoid schizophrenia, to identify further targets of psychocorrection. Materials and methods. On the basis of the psychiatric department of the Transcarpathian regional narcological dispensary 100 women with PS and their husbands were examined during 2014 –2016. Agroup of comparison comprised of 50 husbands of mentally healthy women. Results. The specific manifestations of pathological changes in family interactions in PS women is the prevalence of pathological types and disharmonious family relationships, emotionally detached (65.0%), stress-dissociative (20.0%), symbiotic (9.0%), pseudo-solidarity (3.0%) and hyper-protective (2.0%), decrease feelings of love and sympathy for the wives to their husbands, as well as general reduction in emotional relationships in the couples. Conclusions. The data obtained formed the basis for the development of medical and psychological measures to support families of PS women. Key words: paranoid schizophrenia, women, men, family functioning.